2000
DOI: 10.1016/s0735-1097(99)00599-9
|View full text |Cite
|
Sign up to set email alerts
|

Restenosis and clinical outcome in patients treated with amlodipine after angioplasty: results from the coronary AngioPlasty Amlodipine REStenosis Study (CAPARES)

Abstract: Amlodipine therapy starting two weeks before PTCA did not reduce luminal loss, but the incidence of repeat PTCA and the composite major adverse clinical events were significantly reduced during the four-month follow-up period after PTCA with amlodipine as compared with placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
39
0
9

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(52 citation statements)
references
References 39 publications
4
39
0
9
Order By: Relevance
“…3 In the Circadian Anti-ischemia Program in Europe (CAPE) trial, amlodipine was shown to reduce ischemia in patients with coronary artery disease 8 ; in the Prospective Randomized Evaluation of the Vascular Effects of Norvasc Trial (PREVENT), amlodipine was shown to reduce hospitalizations for unstable angina and revascularization 9 ; and in the Coronary AngioPlasty Amlodipine REStenosis Study (CAPARES), amlodipine was shown to reduce the need for revascularization in patients with stable angina. 10 As recently reviewed in this Journal, the pleiotropic effects of statins 11 might serve to explain some of their unexpected mechanisms and actions, both in vitro and in clinical settings. The same holds true for CCBs.…”
mentioning
confidence: 99%
“…3 In the Circadian Anti-ischemia Program in Europe (CAPE) trial, amlodipine was shown to reduce ischemia in patients with coronary artery disease 8 ; in the Prospective Randomized Evaluation of the Vascular Effects of Norvasc Trial (PREVENT), amlodipine was shown to reduce hospitalizations for unstable angina and revascularization 9 ; and in the Coronary AngioPlasty Amlodipine REStenosis Study (CAPARES), amlodipine was shown to reduce the need for revascularization in patients with stable angina. 10 As recently reviewed in this Journal, the pleiotropic effects of statins 11 might serve to explain some of their unexpected mechanisms and actions, both in vitro and in clinical settings. The same holds true for CCBs.…”
mentioning
confidence: 99%
“…Another important finding of this trial was that amlodipine reduced the rates of unstable angina and coronary revascularization (149). The CAPARES (Coronary Angioplasty Amlodipine Restenosis Study) also showed a reduction of coronary revascularization (150). The vasorelaxant effect of CCBs, i.e., the regulation of NO production, prevents the formation of abnormal vasoconstrictions, which can lead to plaque rupture.…”
Section: Hypertensionmentioning
confidence: 89%
“…Антиангинальное действие амлодипина не уступает таковому других антиангинальных пре-паратов, в первую очередь нитратов и бета-адрено-блокаторов. Антиишемическое действие амлодипи-на у больных СС было продемонстрировано в иссле-довании CAPE [12]. В нем было показано, что при на-значении амлодипина наблюдается существенное уменьшение количества и продолжительности эпи-зодов ишемии миокарда в сравнении с плацебо, причем это действие амлодипина продолжается в тече-ние суток.…”
Section: Discussionunclassified